Effect of HIV self-testing on the number of sexual partners among female sex workers in Zambia. (13th March 2018) - Oldenburg, Catherine E.; Chanda, Michael M.; Ortblad, Katrina F.; Mwale, Magdalene; Chongo, Steven; Kamungoma, Nyambe; Kanchele, Catherine; Fullem, Andrew; Moe, Caitlin; Barresi, Leah G.; Harling, Guy D.; Bärnighausen, Till
Abstract : Objectives: To assess the effect of two health system approaches to distribute HIV self-tests on the number of female sex workers' client and nonclient sexual partners. Design: Cluster randomized controlled trial. Methods: Peer educators recruited 965 participants. Peer educator–participant groups were randomized 1 : 1 : 1 to one of three arms: delivery of HIV self-tests directly from a peer educator, free facility-based delivery of HIV self-tests in exchange for coupons, or referral to standard-of-care HIV testing. Participants in all three arms completed four peer educator intervention sessions, which included counseling and condom distribution. Participants were asked the average number of client partners they had per night at baseline, 1 and 4 months, and the number of nonclient partners they had in the past 12 months (at baseline) and in the past month (at 1 month and 4 months). Results: At 4 months, participants reported significantly fewer clients per night in the direct delivery arm (mean difference −0.78 clients, 95% CI −1.28 to −0.28, P = 0.002) and the coupon arm (−0.71, 95% CI −1.21 to −0.21, P = 0.005) compared with standard of care. Similarly, they reported fewer nonclient partners in the direct delivery arm (−3.19, 95% CI −5.18 to −1.21, P = 0.002) and in the coupon arm (−1.84, 95% CI −3.81 to 0.14, P = 0.07) arm compared with standard of care. Conclusion: Expansion of HIV self-testing may have positive behavioral effects enhancing other HIV prevention efforts among female sex workers in Zambia. Trial Registration: ClinicalTrials.gov NCT02827240.